In search of the right to abortion in the jurisprudence of the Inter-American Court - Gómez, Verónica María (2022)
This article aims to investigate the standards of the Inter-American Human Rights System, seeking to recognize there the features of an incipient right to abortion. As a catalyst, it uses the sanction of Law 27.610 at the end of 2020, in Argentina, which guarantees access to the voluntary interruption of pregnancy during the first fourteen weeks of the gestational process and post-abortion care throughout the national territory. In this framework, it reviews the fundamentals of human rights put forward by the conservative sectors in rejection of the approval of the Law -which are the same that they repeat to detract from its legitimacy in the media and hinder its implementation in the judicial sphere- in order to discredit them in their confrontation with the mentioned standards. In the task of rebuilding them, different sentences of the Inter-American Court are reviewed based on the analysis of four central axes: 1) the gradual or incremental protection of life, 2) the autonomy of pregnant people, 3) the discriminatory character of the norms that criminalize abortion and 4) its framing as gender violence. The goal is to advance in an argumentative network that affirms the conventionality of normative frameworks such as the argentine one, based on the model of terms, and qualifies the criminalization of abortion as a violation of human rights. Make a theoretical contribution that serves to consolidate the voluntary interruption of pregnancy in that country and its extension to others in Latin America.